Nickel-based superalloy, valve sealing surface containing nickel-based superalloy and preparation method of valve sealing surface
By using a specific composition of nickel-based high-temperature alloy and laser cladding process, the sealing surface of the high-temperature and high-pressure valve is solved, and the sealing surface is not tightly sealed or cracked under frequent movements and rapid steam flow changes is significantly improved. Reliability and lifespan.
Patent Information
- Application Number
- CN202411646134.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to meet the long-term use requirements of the sealing surface of high-temperature and high-pressure valves, especially in the case of frequent movements and rapid steam flow changes, resulting in lax sealing or cracking and failure of the sealing surface.
Using a nickel-based high-temperature alloy with a specific composition and content proportion, and combining laser cladding technology to prepare the valve sealing surface to improve its hardness and mechanical properties, and can withstand the alternation caused by frequent contact impacts between the valve core and the valve seat and steam erosion. stress.
It significantly improves the reliability and life of the sealing surface of high-temperature and high-pressure valves, ensuring the stability and effectiveness of the sealing surface under harsh working conditions.
Smart Images

Figure BDA0005139742670000151 
Figure BDA0005139742670000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steam turbines, and in particular to a nickel-based high-temperature alloy, a valve sealing surface containing the same, and a method for preparing the valve sealing surface. Background Art
[0002] With the acceleration of the construction of new power systems and the development of the power spot market, thermal power units are more involved in deep peak regulation, which puts forward higher requirements on the peak regulation adaptability of steam turbine units. During the deep peak regulation process, the high-temperature and high-pressure valves of the steam turbine will move more frequently, and the steam flow will change rapidly, causing the valve core and valve seat to frequently contact and collide. In addition, the valve core and valve seat are subjected to alternating stress caused by steam scouring, which eventually leads to problems such as poor valve sealing and even cracking and failure of the sealing surface under long-term operation, affecting the economy and safety of the unit operation.
[0003] After in-depth research on the materials and working conditions of valve sealing surfaces, it was found that cobalt-based alloys represented by Stellite 6# have gradually failed to meet the long-term use requirements of high-temperature and high-pressure valve sealing surfaces in new power systems due to their inherent defects. In addition, cobalt-based alloys are expensive and scarce, which limits their application in valve sealing surface materials. Nickel-based alloys have excellent high-temperature friction resistance, heat corrosion resistance and heat fatigue resistance, and are increasingly widely used as valve sealing surfaces. Inconel625 is a nickel-based high-temperature alloy known for its good high-temperature strength, oxidation resistance and corrosion resistance. However, its main problems in high-temperature and high-pressure valve sealing surfaces are as follows: (1) The strength of Inconel625 nickel-based high-temperature alloy is relatively low, and its mechanical properties are relatively poor, making it difficult to meet the stringent use requirements of valve sealing surfaces; (2) The hardness of Inconel625 nickel-based high-temperature alloy is relatively low, making it difficult to withstand the alternating stresses caused by frequent contact and collision between the valve core and the valve seat, steam scouring and temperature changes, which can easily cause damage to the valve sealing surface.
[0004] Therefore, providing an alloy material suitable for the sealing surface of a high-temperature and high-pressure valve of a steam turbine and a method for preparing the valve sealing surface is a technical problem that needs to be solved in the current field. Summary of the invention
[0005] In view of the above problems, the purpose of the present invention is to provide a nickel-based high-temperature alloy, a valve sealing surface containing the same, and a method for preparing the valve sealing surface. Compared with the prior art, the nickel-based high-temperature alloy provided by the present invention has good hardness and mechanical properties. By combining it with the laser cladding method, the obtained valve sealing surface can withstand the alternating stress generated by frequent contact and collision between the valve core and the valve seat and steam scouring, thereby significantly improving the reliability and life of the high-temperature and high-pressure valve sealing surface.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a nickel-based high-temperature alloy, which comprises, in terms of mass percentage, the following: C: 0.05-0.20%, Mn: 0.30-0.60%, Si: 0.20-0.60%, P: ≤0.015%, S: ≤0.015%, Fe: 2.0-6.0%, Cr: 20-25%, Mo: 6-10%, Nb: 3-5%, W: 8-12%, Al: 0.2-0.5%, Ti: 0.1-0.8%, and the balance is Ni.
[0008] In the present invention, by controlling the composition and mass percentage of the nickel-based high-temperature alloy, the hardness of the nickel-based high-temperature alloy can be significantly improved, and the alloy can have good mechanical properties. When used to prepare the valve sealing surface, the alloy can withstand the alternating stress generated by frequent contact and impact between the valve core and the valve seat and steam scouring, thereby significantly improving the reliability and life of the high-temperature and high-pressure valve sealing surface.
[0009] In the present invention, the nickel-based high-temperature alloy contains 0.05-0.20% C, for example, it can be 0.05%, 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.16%, 0.18% or 0.20%, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable; it contains 0.30-0.60% Mn, for example, it can be 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55% or 0.60%, but it is not limited to the listed values, and other values not listed in the numerical range are also applicable; it contains 0.20-0.60% Si, for example, it can be 0.20%, 0.25%, 0.30%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55% or 0.60%, but not limited to the listed values, other values not listed in the numerical range are also applicable; containing ≤0.015% P, for example, it can be 0.015%, 0.014%, 0.013%, 0.012%, 0.011% or 0.010%, but not limited to the listed values, other values not listed in the numerical range are also applicable; containing: ≤0.015% S, for example, it can be 0.015%, 0.014%, 0.013%, 0.012%, 0.011% or 0.010%, but not limited to the listed values, other values not listed in the numerical range are also applicable; containing 2.0-6 .0% Fe, for example, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5% or 6.0%, but not limited to the listed values, and other values not listed in the numerical range are also applicable; 20-25% Cr, for example, 20%, 21%, 22%, 23%, 24% or 25%, but not limited to the listed values, and other values not listed in the numerical range are also applicable; 6-10% Mo, for example, 6%, 7%, 8%, 9% or 10%, but not limited to the listed values, and other values not listed in the numerical range are also applicable; 3-5% Nb, for example, 3%, 3.5%, 4%, 4.5% or 5 %, but not limited to the listed values, and other values not listed within the numerical range are equally applicable; containing 8-12% W, for example, 8%, 9%, 10%, 11% or 12%, but not limited to the listed values, and other values not listed within the numerical range are equally applicable; containing 0.2-0.5% Al, for example, 0.2%, 0.3%, 0.4% or 0.5%, but not limited to the listed values, and other values not listed within the numerical range are equally applicable; containing 0.1-0.8% Ti, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7% or 0.8%, but not limited to the listed values, and other values not listed within the numerical range are equally applicable.
[0010] Preferably, the mass ratio of W to Mo in the nickel-based high-temperature alloy is (1.2-1.5):1, for example, it can be 1.2:1, 1.3:1, 1.4:1 or 1.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] The present invention can further improve the hardness and mechanical properties of the nickel-based high-temperature alloy by optimally controlling and adopting the above-mentioned mass ratio.
[0012] In a second aspect, the present invention provides a valve sealing surface, wherein the valve sealing surface comprises the nickel-based high-temperature alloy described in the first aspect of the present invention.
[0013] In a third aspect, the present invention provides a method for preparing the valve sealing surface according to the second aspect of the present invention, the preparation method comprising the following steps:
[0014] (1) mixing raw material powders according to the elements and mass percentages of the nickel-based high-temperature alloy, and then ball milling to obtain cladding powder;
[0015] (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program;
[0016] (3) Using the cladding powder obtained in step (1), laser cladding is performed on the sealing surface according to the digital control program obtained in step (2), and then heat treatment and grinding are performed in sequence to obtain a valve sealing surface.
[0017] In the present invention, by using a nickel-based high-temperature alloy with a specific composition and content ratio and combining it with a specific laser cladding process to prepare the valve sealing surface, it has the following advantages: (1) Laser cladding has a low requirement for preheating temperature, and the cladding process is relatively simple, with a high degree of automation and a high production yield; (2) There will be no obvious migration of elements such as Fe and C at the interface between the nickel-based high-temperature alloy cladding layer and the parent material (such as T / P91 steel), the interface area has a stable structure, and the welding residual stress is small; (3) The nickel-based high-temperature alloy has good high-temperature performance, crack resistance, corrosion resistance, oxidation resistance and thermal corrosion resistance under the high temperature of laser cladding. In summary, the preparation method provided by the present invention can effectively improve the high-temperature performance and reliability of the valve sealing surface by combining the nickel-based high-temperature alloy and the laser cladding process, and prepare a nickel-based alloy sealing surface with excellent comprehensive performance to replace the traditional Stellite 6# alloy sealing surface, which is of great significance for improving the reliability and life of the high-temperature and high-pressure valve sealing surface, and can generate good economic value.
[0018] In the present invention, the Stellite 6# is a cobalt-based alloy well known in the art, which is based on cobalt and contains alloy elements such as chromium, tungsten, molybdenum, carbon, etc. In the present invention, the grinding is used to ensure the sealing of the valve sealing surface.
[0019] Preferably, the raw material powders in step (1) are dried before mixing.
[0020] Preferably, the temperature of the drying treatment is 100-200°C, for example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the drying time is 3-5 h, for example, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, the particle size of the raw powder is 80-270 mesh, for example, it can be 80 mesh, 90 mesh, 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh or 270 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In the present invention, the raw material powder is a single substance or alloy containing constituent elements of a nickel-based high-temperature alloy.
[0024] Preferably, the rotation speed of the ball mill in step (1) is 10-15 r / min, for example, it can be 10 r / min, 11 r / min, 12 r / min, 13 r / min, 14 r / min or 15 r / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] Preferably, the ball milling time is 20-25 h, for example, 20 h, 21 h, 22 h, 23 h, 24 h or 25 h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the particle size of the cladding powder is 100-270 mesh, for example, it can be 100 mesh, 110 mesh, 120 mesh, 130 mesh, 140 mesh, 150 mesh, 160 mesh, 170 mesh, 180 mesh, 190 mesh, 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh or 270 mesh, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] Preferably, the laser cladding in step (3) includes: conveying cladding powder to the molten pool by using a protective gas for cladding.
[0028] Preferably, the protective gas comprises argon.
[0029] Preferably, the flow rate of the argon gas is 10-20 L / min, for example, it can be 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min, 16 L / min, 17 L / min, 18 L / min, 19 L / min or 20 L / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the purity of the argon gas is ≥ 99.99%, for example, it may be 99.99%, 99.991%, 99.992%, 99.993%, 99.994% or 99.995%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the powder feeding rate of the cladding powder is 10-15 g / min, for example, it can be 10 g / min, 11 g / min, 12 g / min, 13 g / min, 14 g / min or 15 g / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In the present invention, by preferably controlling the powder feeding rate of the cladding powder, the powder can be completely melted during the laser cladding process, achieving sufficient metallurgical bonding, avoiding the formation of unmelted particles that affect the cladding quality, and further improving the hardness and mechanical properties of the sealing surface.
[0033] Preferably, the laser used for the laser cladding in step (3) comprises a fiber laser.
[0034] Preferably, the diameter of the light spot used for the laser cladding is 3-5 mm, for example, 3 mm, 4 mm or 5 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, the laser power used for laser cladding is 1000-1500 W, for example, it can be 1000 W, 1050 W, 1100 W, 1150 W, 1200 W, 1250 W, 1300 W, 1350 W, 1400 W, 1450 W or 1500 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In the present invention, by optimally controlling the laser power used for laser cladding, the cladding quality of the cladding layer can be effectively controlled, and the cladding layer formed under the appropriate laser power has a good appearance, and the width and depth of the cladding layer are within a reasonable range. When the laser power is too low, the surface of the parent material cannot be fully melted, and the laser cladding forming is incomplete, resulting in a narrow width and shallow depth of the cladding layer; when the laser power is too high, it is easy to cause holes in the cladding layer or overflow of the molten pool, and the cladding layer is also poorly formed.
[0037] Preferably, the laser scanning rate used for the laser cladding is 8-12 mm / s, for example, 8 mm / s, 9 mm / s, 10 mm / s, 11 mm / s or 12 mm / s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In the present invention, by preferably controlling the laser scanning rate used in laser cladding, the cladding quality of the cladding layer can be effectively controlled, and the appropriate scanning speed can reduce the heat-affected zone of the cladding layer and reduce the risk of deformation and stress concentration. When the laser scanning rate is too fast, the laser irradiation time is too short, resulting in the formation of a discontinuous molten pool during the cladding process, and the cladding layer may be discontinuous and the parent material may not be partially melted; when the laser scanning rate is too slow, the laser irradiation time is too long, the weld pool is too deep, and the seam morphology is prone to convex, deformation or cracking.
[0039] Preferably, the laser heat input used in the laser cladding is 60-90 J / mm 2 , for example, it can be 60J / mm 2 、62J / mm 2 、65J / mm 2 、68J / mm 2 、70J / mm 2 、72J / mm 2 , 75J / mm 2 、78J / mm 2 、80J / mm 2 、82J / mm 2 、85J / mm 2 、88J / mm 2 or 90J / mm 2 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0040] Preferably, the heat treatment in step (3) comprises: first heating up to a first end point temperature at a certain heating rate and keeping the temperature, and then cooling down to a second end point temperature at a certain cooling rate.
[0041] Preferably, the heating rate is ≤100°C / h, for example, it can be 100°C / h, 98°C / h, 95°C / h, 92°C / h, 90°C / h, 88°C / h, 85°C / h, 82°C / h or 80°C / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the first endpoint temperature is 700-760°C, for example, it can be 700°C, 720°C, 740°C, 742°C, 744°C, 746°C, 748°C, 750°C, 752°C, 754°C, 756°C, 758°C or 760°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] Preferably, the insulation time is 0.5-1.5h, for example, it can be 0.5h, 0.6h, 0.8h, 1h, 1.1h, 1.2h, 1.4h or 1.6h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the cooling rate is ≤100°C / h, for example, it can be 100°C / h, 98°C / h, 95°C / h, 92°C / h, 90°C / h, 88°C / h, 85°C / h, 82°C / h or 80°C / h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the second endpoint temperature is 200-300°C, for example, it can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0047] (1) drying a raw material powder with a particle size of 80-270 mesh at a temperature of 100-200° C. for 3-5 hours, mixing the raw material powder according to the elements and mass percentages contained in the nickel-based high-temperature alloy, and then ball milling for 20-25 hours at a rotation speed of 10-15 r / min to obtain a cladding powder with a particle size of 100-270 mesh;
[0048] (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program;
[0049] (3) using the cladding powder obtained in step (1), and laser cladding the sealing surface according to the digital control program obtained in step (2), the laser cladding comprising conveying the cladding powder to the molten pool for cladding using a protective gas, the protective gas comprising argon, the flow rate of the argon being 10-20 L / min, the purity of the argon being ≥99.99%, the powder feeding rate of the cladding powder being 10-15 g / min, the laser used for the laser cladding comprising a fiber laser, the spot diameter being 3-5 mm, the laser power being 1000-1500 W, the laser scanning rate being 8-12 mm / s, and the laser heat input being 60-90 J / mm 2 , then heat up to the first end temperature of 700-760°C at a heating rate of ≤100°C / h and keep warm for 0.5-1.5h, then cool down to the second end temperature of 200-300°C at a cooling rate of ≤100°C / h, and then grind to obtain the valve sealing surface.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The nickel-based high-temperature alloy provided by the present invention can significantly improve the hardness of the nickel-based high-temperature alloy by adopting a specific composition and content ratio, and make it have good mechanical properties. Under optimal conditions, the hardness can reach above 306HB, and the plastic extension strength R p0.2 Reaching above 603MPa, the tensile strength R m Reach above 941MPa, and the elongation after break A reaches above 31%.
[0052] (2) The valve sealing surface preparation method provided by the present invention adopts a nickel-based high-temperature alloy with a specific composition and content ratio and combines it with a specific laser cladding process. The prepared valve sealing surface can withstand the alternating stress generated by frequent contact and impact between the valve core and the valve seat and steam scouring, thereby significantly improving the reliability and life of the high-temperature and high-pressure valve sealing surface. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Example 1
[0055] The present embodiment provides a nickel-based high-temperature alloy for a valve sealing surface, and the nickel-based high-temperature alloy includes, in terms of mass percentage, the following components: C: 0.08%, Mn: 0.42%, Si: 0.38%, P: 0.010%, S: 0.009%, Fe: 3.5%, Cr: 21%, Mo: 7%, Nb: 4.1%, W: 10.50%, Al: 0.30%, Ti: 0.21%, and the remainder is Ni.
[0056] This embodiment also provides a valve sealing surface containing the above nickel-based high-temperature alloy and a preparation method thereof. Taking the valve sealing surface made of F91 steel as an example, the preparation method includes the following steps:
[0057] (1) drying a raw material powder with a particle size of 80-270 mesh at a temperature of 150° C. for 4 h, mixing the raw material powder according to the elements and mass percentages contained in the nickel-based high-temperature alloy, and then ball milling for 22 h at a rotation speed of 12 r / min to obtain a cladding powder with a particle size of 100-270 mesh;
[0058] (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program;
[0059] (3) using the cladding powder obtained in step (1), and laser cladding the sealing surface according to the digital control program obtained in step (2), the laser cladding includes conveying the cladding powder to the molten pool for cladding by using argon gas, the flow rate of the argon gas is 15 L / min, the purity of the argon gas is ≥99.99%, the powder feeding rate of the cladding powder is 12 g / min, the laser used for the laser cladding is a fiber laser, the spot diameter is 4 mm, the laser power is 1200 W, the laser scanning rate is 10 mm / s, and the laser heat input is 80 J / mm 2 , then the temperature is increased at a heating rate of 100°C / h to a first end temperature of 750°C and kept at this temperature for 1h, then the temperature is decreased at a cooling rate of 100°C / h to a second end temperature of 250°C, and then ground to obtain a valve sealing surface.
[0060] Example 2
[0061] The present embodiment provides a nickel-based high-temperature alloy for a valve sealing surface, wherein the nickel-based high-temperature alloy includes, in terms of mass percentage, the following components: C: 0.05%, Mn: 0.47%, Si: 0.38%, P: 0.008%, S: 0.010%, Fe: 6%, Cr: 20%, Mo: 8%, Nb: 3.2%, W: 12%, Al: 0.21%, Ti: 0.35%, and the remainder is Ni.
[0062] This embodiment also provides a valve sealing surface containing the above nickel-based high-temperature alloy and a preparation method thereof. Taking the valve sealing surface made of F91 steel as an example, the preparation method includes the following steps:
[0063] (1) drying a raw material powder with a particle size of 80-270 mesh at a temperature of 100° C. for 5 h, mixing the raw material powder according to the elements and mass percentages contained in the nickel-based high-temperature alloy, and then ball milling for 20 h at a rotation speed of 10 r / min to obtain a cladding powder with a particle size of 100-270 mesh;
[0064] (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program;
[0065] (3) using the cladding powder obtained in step (1), and laser cladding the sealing surface according to the digital control program obtained in step (2), the laser cladding includes conveying the cladding powder to the molten pool for cladding by using argon gas, the flow rate of the argon gas is 20 L / min, the purity of the argon gas is ≥99.99%, the powder feeding rate of the cladding powder is 10 g / min, the laser used for the laser cladding is a fiber laser, the spot diameter is 5 mm, the laser power is 1000 W, the laser scanning rate is 12 mm / s, and the laser heat input is 60 J / mm 2 , then the temperature is increased at a heating rate of 95°C / h to a first end temperature of 740°C and kept at this temperature for 1.5h, then the temperature is decreased at a cooling rate of 95°C / h to a second end temperature of 200°C, and then ground to obtain a valve sealing surface.
[0066] Example 3
[0067] The present embodiment provides a nickel-based high-temperature alloy for a valve sealing surface, and the nickel-based high-temperature alloy includes, in terms of mass percentage, the following: C: 0.16%, Mn: 0.53%, Si: 0.58%, P: 0.011%, S: 0.011%, Fe: 3.5%, Cr: 24.2%, Mo: 6%, Nb: 4.5%, W: 9%, Al: 0.37%, Ti: 0.18%, and the remainder is Ni.
[0068] This embodiment also provides a valve sealing surface containing the above nickel-based high-temperature alloy and a preparation method thereof. Taking the valve sealing surface made of F91 steel as an example, the preparation method includes the following steps:
[0069] (1) drying a raw material powder with a particle size of 80-270 mesh at a temperature of 200° C. for 3 h, mixing the raw material powder according to the elements and mass percentages contained in the nickel-based high-temperature alloy, and then ball milling for 25 h at a rotation speed of 15 r / min to obtain a cladding powder with a particle size of 100-270 mesh;
[0070] (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program;
[0071] (3) using the cladding powder obtained in step (1), and laser cladding the sealing surface according to the digital control program obtained in step (2), the laser cladding includes conveying the cladding powder to the molten pool for cladding by using argon gas, the flow rate of the argon gas is 10 L / min, the purity of the argon gas is ≥99.99%, the powder feeding rate of the cladding powder is 15 g / min, the laser used for the laser cladding is a fiber laser, the spot diameter is 3 mm, the laser power is 1500 W, the laser scanning rate is 8 mm / s, and the laser heat input is 90 J / mm 2 , then the temperature is increased at a heating rate of 90°C / h to a first end temperature of 760°C and kept at this temperature for 0.5h, then the temperature is decreased at a cooling rate of 90°C / h to a second end temperature of 300°C, and then ground to obtain a valve sealing surface.
[0072] Example 4
[0073] This embodiment provides a nickel-based high-temperature alloy for a valve sealing surface. The difference between the nickel-based high-temperature alloy and Embodiment 1 is that only the mass percentage of W and Ni is changed, so that the mass percentage of W is 6%.
[0074] This embodiment also provides a valve sealing surface containing the above-mentioned nickel-based high-temperature alloy and a preparation method thereof. The difference between the preparation method and Example 1 is only that a mixed raw material powder with the elements and mass percentages contained in the nickel-based high-temperature alloy in this embodiment is used.
[0075] Example 5
[0076] This embodiment provides a nickel-based high-temperature alloy for a valve sealing surface. The difference between the nickel-based high-temperature alloy and Embodiment 1 is that only the mass percentage of W and Ni is changed, so that the mass percentage of W is 14%.
[0077] This embodiment also provides a valve sealing surface containing the above-mentioned nickel-based high-temperature alloy and a preparation method thereof. The difference between the preparation method and Example 1 is only that a mixed raw material powder with the elements and mass percentages contained in the nickel-based high-temperature alloy in this embodiment is used.
[0078] Example 6
[0079] This embodiment provides a nickel-based high-temperature alloy for a valve sealing surface. The difference between the nickel-based high-temperature alloy and Embodiment 1 is that only the mass percentage of W and Mo is changed, so that the mass ratio of W to Mo in the nickel-based high-temperature alloy is 2:1.
[0080] This embodiment also provides a valve sealing surface containing the above-mentioned nickel-based high-temperature alloy and a preparation method thereof. The difference between the preparation method and Example 1 is only that a mixed raw material powder with the elements and mass percentages contained in the nickel-based high-temperature alloy in this embodiment is used.
[0081] Example 7
[0082] This embodiment provides a nickel-based high-temperature alloy for a valve sealing surface. The difference between the nickel-based high-temperature alloy and Embodiment 1 is that only the mass percentage of W and Mo is changed, so that the mass ratio of W to Mo in the nickel-based high-temperature alloy is 1:1.
[0083] This embodiment also provides a valve sealing surface containing the above-mentioned nickel-based high-temperature alloy and a preparation method thereof. The difference between the preparation method and Example 1 is only that a mixed raw material powder with the elements and mass percentages contained in the nickel-based high-temperature alloy in this embodiment is used.
[0084] Example 8
[0085] This embodiment provides a method for preparing a valve sealing surface. The difference between the preparation method and Embodiment 1 is that the powder feeding rate of the cladding powder is 8 g / min.
[0086] Example 9
[0087] This embodiment provides a method for preparing a valve sealing surface. The difference between the preparation method and Embodiment 1 is that the powder feeding rate of the cladding powder is 18 g / min.
[0088] Compared with Example 1, the powder feeding rates of Examples 8-9 are not within the preferred range of the present invention, resulting in the quality of the cladding layer being unable to meet the production requirements of the valve sealing surface. It can be seen that the present invention can further ensure that the powder is completely melted during the cladding process by preferentially controlling the powder feeding rate, thereby achieving sufficient metallurgical bonding and ensuring the forming and mechanical properties of the valve sealing surface.
[0089] Example 10
[0090] This embodiment provides a method for preparing a valve sealing surface. The only difference between the preparation method and Embodiment 1 is that the laser power is 800W.
[0091] Embodiment 11
[0092] This embodiment provides a method for preparing a valve sealing surface. The only difference between the preparation method and Embodiment 1 is that the laser power is 1700W.
[0093] The only difference between Example 10-11 and Example 1 is that the laser power is not within the preferred range of the present invention. When the laser power is too low, the base material cannot be fully melted. When the laser power is too high, holes appear in the cladding layer or the molten pool overflows. Ultimately, the quality of the cladding layer cannot meet the requirements. It can be seen that the present invention can further effectively control the quality of the cladding layer by preferentially controlling the laser power, so that the cladding layer has a good appearance and the mechanical properties meet the requirements.
[0094] Example 12
[0095] This embodiment provides a method for preparing a valve sealing surface. The only difference between the preparation method and Embodiment 1 is that the laser scanning rate is 6 mm / s.
[0096] Embodiment 13
[0097] This embodiment provides a method for preparing a valve sealing surface. The only difference between the preparation method and Embodiment 1 is that the laser scanning rate is 14 mm / s.
[0098] The only difference between Examples 12-13 and Example 1 is that the laser scanning rate is not within the preferred range of the present invention. When the laser scanning rate is too slow, the seam morphology is prone to protrusion, deformation or cracking. When the laser scanning rate is too fast, the cladding layer may be discontinuous and the parent material may not be partially melted. It can be seen that the present invention can further effectively control the quality of the cladding layer by preferentially controlling the laser scanning rate, reduce the risk of deformation and stress concentration, and achieve the required mechanical properties.
[0099] Comparative Example 1
[0100] The present comparative example provides an Inconel625 nickel-based high-temperature alloy, which contains, by mass percentage, 0.07% C, 0.38% Mn, 0.43% Si, 0.011% P, 0.012% S, 3.5% Fe, 20% Cr, 10% Mo, 3.33% Nb, 0.68% Co, 0.32% Al, 0.21% Ti, and the balance is Ni.
[0101] This comparative example provides a method for preparing a valve sealing surface. The difference between the preparation method and Example 1 is that a mixed raw material powder with the elements and mass percentages of the Inconel 625 nickel-based high-temperature alloy in this comparative example is used.
[0102] Comparative Example 2
[0103] The present comparative example provides a Stellite 6# alloy, which, in terms of mass percentage, contains C: 1.11%; Mn: 0.48%; Si: 1.05%; P: 0.009%; S: ≤0.008%; Fe: 3.0%; Cr: 29.0%; Mo: 1.04%; W: 4.07%; Ni: 3.10%; and the balance is Co.
[0104] This comparative example provides a method for preparing a valve sealing surface. The difference between the preparation method and Example 1 is that a mixed raw material powder with the elements and mass percentages of the Stellite 6# alloy in this comparative example is used.
[0105] The cladding layer forming conditions in Examples 1-7 and Comparative Examples 1-2 are shown in Table 1. The hardness of the valve sealing surfaces prepared in Examples 1-7 and Comparative Examples 1-2 was tested according to the standard GB / T231.1-2018 "Metallic Materials Brinell Hardness Test Part 1: Test Method", and the plastic extension strength, tensile strength and elongation after fracture of the valve sealing surfaces prepared in Examples 1-7 and Comparative Examples 1-2 were tested according to the standard GB / T 228.1-2021 "Metallic Materials Room Temperature Tensile Test Method", and the results are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] From the data in Table 1, we can see the following points:
[0110] (1) From the data of Examples 1-3, it can be seen that under optimal conditions, the nickel-based high-temperature alloy provided by the present invention can achieve a hardness of more than 306 HB, a plastic extension strength of more than 603 MPa, a tensile strength of more than 941 MPa, and an elongation after fracture of more than 31%.
[0111] (2) A comprehensive comparison of the data of Example 1 and Examples 4-5 shows that the only difference between Example 4-5 and Example 1 is that the mass percentage of W is not within the preferred range of the present invention. The mass percentage of W in Example 4 is too low, resulting in a significant decrease in hardness, plastic elongation strength and tensile strength. The mass percentage of W in Example 5 is too high, resulting in a significant decrease in elongation after fracture. It can be seen that the present invention can further ensure good hardness and strength by optimally controlling the mass percentage of W, thereby achieving good elongation after fracture, so that the valve sealing surface has excellent comprehensive performance.
[0112] (3) Comprehensive comparison of the data of Example 1 and Examples 6-7 shows that the only difference between Example 6-7 and Example 1 is that the mass ratio of W to Mo is not within the preferred range of the present invention. The mass ratio of W to Mo in Example 6 is 2:1, which leads to a significant decrease in elongation after fracture. The mass ratio of W to Mo in Example 7 is 1:1, which leads to a significant decrease in hardness, plastic extension strength and tensile strength. It can be seen that the present invention can further ensure good hardness and strength while achieving good elongation after fracture by optimally controlling the mass ratio of W to Mo, so that the valve sealing surface has excellent comprehensive performance.
[0113] (4) Comprehensive comparison of the data of Example 1 and Comparative Examples 1-2 shows that Example 1 has excellent hardness, plastic elongation strength and tensile strength, as well as good elongation after fracture, compared with the Inconel625 nickel-based high-temperature alloy provided in Comparative Example 1 and the Stellite 6# alloy provided in Comparative Example 2. It can be seen that the nickel-based high-temperature alloy provided by the present invention has excellent comprehensive performance.
[0114] In summary, the nickel-based high-temperature alloy provided by the present invention has good hardness and mechanical properties. By combining it with the laser cladding method, the resulting valve sealing surface can withstand the alternating stress generated by frequent contact and impact between the valve core and the valve seat and steam scouring, thereby significantly improving the reliability and life of the high-temperature and high-pressure valve sealing surface.
[0115] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A nickel-based high-temperature alloy, characterized in that: The nickel-based high-temperature alloy includes, by mass percentage, C: 0.05-0.20%, Mn: 0.30-0.60%, Si: 0.20-0.60%, P: ≤0.015%, S: ≤0.015%, Fe: 2.0-6.0%, Cr: 20-25%, Mo: 6-10%, Nb: 3-5%, W: 8-12%, Al: 0.2-0.5%, Ti: 0.1-0.8%, and the balance is Ni.
2. The nickel-based high-temperature alloy according to claim 1, characterized in that: The mass ratio of W to Mo in the nickel-based high-temperature alloy is (1.2-1.5):
1.
3. A valve sealing surface, characterized in that: The valve sealing surface contains the nickel-based high-temperature alloy as described in claim 1 or 2.
4. A method for preparing a valve sealing surface as claimed in claim 3, characterized in that: The preparation method comprises the following steps: (1) mixing raw material powders according to the elements and mass percentages of the nickel-based high-temperature alloy, and then ball milling to obtain cladding powder; (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program; (3) Using the cladding powder obtained in step (1), laser cladding is performed on the sealing surface according to the digital control program obtained in step (2), and then heat treatment and grinding are performed in sequence to obtain a valve sealing surface.
5. The preparation method according to claim 4, characterized in that: Step (1) drying the raw material powders before mixing; Preferably, the drying temperature is 100-200°C; Preferably, the drying time is 3-5 hours; Preferably, the particle size of the raw material powder is 80-270 mesh.
6. The preparation method according to claim 4 or 5, characterized in that: The rotation speed of the ball mill in step (1) is 10-15 r / min; Preferably, the ball milling time is 20-25h; Preferably, the particle size of the cladding powder is 100-270 mesh.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The laser cladding in step (3) includes: transporting cladding powder to a molten pool by using a protective gas for cladding; Preferably, the protective gas comprises argon; Preferably, the flow rate of the argon gas is 10-20 L / min; Preferably, the purity of the argon gas is ≥99.99%; Preferably, the feeding rate of the cladding powder is 10-15 g / min.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The laser used in the laser cladding in step (3) comprises a fiber laser; Preferably, the diameter of the spot used for laser cladding is 3-5 mm; Preferably, the laser power used for the laser cladding is 1000-1500W; Preferably, the laser scanning rate used in the laser cladding is 8-12 mm / s; Preferably, the laser heat input used in the laser cladding is 60-90 J / mm 2 .
9. The preparation method according to any one of claims 4 to 8, characterized in that: The heat treatment in step (3) includes: firstly heating the temperature to a first end point temperature at a certain heating rate and keeping the temperature, and then cooling the temperature to a second end point temperature at a certain cooling rate; Preferably, the heating rate is ≤100°C / h; Preferably, the first endpoint temperature is 700-760°C; Preferably, the insulation time is 0.5-1.5h; Preferably, the cooling rate is ≤100°C / h; Preferably, the second end point temperature is 200-300°C.
10. The preparation method according to any one of claims 4 to 9, characterized in that: The preparation method comprises the following steps: (1) drying a raw material powder with a particle size of 80-270 mesh at a temperature of 100-200° C. for 3-5 hours, mixing the raw material powder according to the elements and mass percentages contained in the nickel-based high-temperature alloy, and then ball milling for 20-25 hours at a rotation speed of 10-15 r / min to obtain a cladding powder with a particle size of 100-270 mesh; (2) Slice the three-dimensional CAD image of the valve in layers, extract the sealing surface contour generated by the slicing, design the scanning path and convert it into a digital control program; (3) using the cladding powder obtained in step (1), and laser cladding the sealing surface according to the digital control program obtained in step (2), the laser cladding comprising conveying the cladding powder to the molten pool for cladding using a protective gas, the protective gas comprising argon, the flow rate of the argon being 10-20 L / min, the purity of the argon being ≥99.99%, the powder feeding rate of the cladding powder being 10-15 g / min, the laser used for the laser cladding comprising a fiber laser, the spot diameter being 3-5 mm, the laser power being 1000-1500 W, the laser scanning rate being 8-12 mm / s, and the laser heat input being 60-90 J / mm 2 , then heat up to the first end temperature of 700-760°C at a heating rate of ≤100°C / h and keep warm for 0.5-1.5h, then cool down to the second end temperature of 200-300°C at a cooling rate of ≤100°C / h, and then grind to obtain the valve sealing surface.
Citation Information
Cited By
Laser cladding method for sealing surface of valve seat
CN120006286A
A laser cladding method for a valve seat sealing surface
CN120006286B